1956
DOI: 10.1039/an9568100598
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of the aniline acetate-furfural method for the determination of pentose

Abstract: The aniline concentration and rea,ction temperature of the method of Reeves and Munro have been modified, with an increase in sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

1958
1958
1987
1987

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…3 mg/g WS was reached and dry weight accumulatio~l ceased for a period. All nutrients continued to be taken up during 7,1961 this period. After the dry weight 'step' the uptalte of all nutrients was linearly proportional to the dry weight until the time of glucose exhaustion.…”
Section: Cl~a?zges Ilz Ptimentioning
confidence: 91%
See 3 more Smart Citations
“…3 mg/g WS was reached and dry weight accumulatio~l ceased for a period. All nutrients continued to be taken up during 7,1961 this period. After the dry weight 'step' the uptalte of all nutrients was linearly proportional to the dry weight until the time of glucose exhaustion.…”
Section: Cl~a?zges Ilz Ptimentioning
confidence: 91%
“…VOL. 7,1961 suggested that there might also be internal reserves of magnesium. The third experiment was designed t o explore these possibilities.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…and Jeffreys [98], que também examinaram o efeito da concentração de anilina na reação com o furfural. Descobriu-se que aumentar a concentração de anilina resulta em maior intensidade de cor e um tempo mais curto para atingir o máximo de absorbância.…”
Section: Otimizaçãounclassified